REVIEW OF CRIMINAL LAW IN PROVIDING LEGAL PROTECTION TO CRIME VICTIMS IN THE JUSTICE SYSTEM CRIME IN INDONESIA - Ilmuwani Lubis; Karolus Agung Dery Rianto; Irfan Rizky Pradya; Willy Novan Prakoso; Syaiful Asmi Hasibuan (PT. Radja Intercontinental Publishing, 2023)
There is relatively little attention paid to victims of criminal acts as can be seen in the Criminal Code which only formulates the rights of victims of criminal acts in one article, namely Article 14 c paragraph (1) which regulates the right to compensation for victims of criminal acts of a criminal nature. civil. The Criminal Procedure Code also regulates the rights of victims of criminal acts in Articles 98-101, which regulates combining claims for compensation with criminal cases. In the practice of criminal justice in Indonesia, it can be said that almost no judges make decisions based on the articles mentioned above. The problem in this research is what is the position and role of victims of criminal acts in the criminal justice system in Indonesia; What is the criminal law policy through the responsibilities of the Criminal Justice apparatus in providing legal protection to victims of criminal acts in the criminal justice system in Indonesia; How to provide legal protection to victims of criminal acts in the criminal justice system in the future. This research uses a sociological juridical approach. This research is a type of research that combines a normative approach and a sociological approach. This means that in addition to studying the law in a theoretical context, we also see directly what is happening in society. The research results show that the right to protection and restoration of legal interests in the criminal justice process is as stated in Law Number 8 of 1981 concerning the Criminal Procedure Code and is also formulated morally in Declaration of Basic Principles of Justice for Victims of Crime and abuse of Power, which includes: ways to obtain justice and fair treatment, including, among other things, the right to a mechanism for obtaining justice; has the right to obtain compensation for the suffering he has suffered; It is possible to obtain compensation using formal procedures (law) or informally (by arbitration, customary practices or customary law), which are fast, honest, cheap and acceptable. However, in reality the victim does not get anything.